Sedimentary-diagenetic characteristics and genesis of the Upper Cambrian reservoirs in the Tabei area, Tarim Basin, NW China - Jun Li; Kaibo Shi; Bo Liu; Yongsheng Ma; Yuanchong Wang; Qing He; Jiaming Deng; Xichuan Men; Xiangyu Bai; Jianhao Hua (Journal of Asian Earth Sciences, 2026)

Strain-specific fermentation reshapes aroma-active volatiles and antioxidant-related properties of soy protein isolate-based plant milk - Hanhan Shi; Jiaming Li; Tanxu Tang; Tianzhi Qu; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2026)

Electrochemically crosslinked poly(arylene ether sulfone)-triphenylamine electrochromic polymer networks for smart windows - Keying Feng; Zhen Xing; Xiangfu Shi; Jiaming Tian; Hao Zhang; Zong-Quan Wu; Zheng Chen; Zhenhua Jiang (Chemical Engineering Journal, 2026)

High-accuracy estimation of global site-level soil heterotrophic respiration through Geo-XGBoost integration with expanded datasets and remote sensing - Jie Liu; Ni Huang; Luying Zhu; Jiaming Chang; Yuting Shi; Zheng Niu; Dewen Cai; Li Wang (Agricultural and Forest Meteorology, 2026)

Catchment land use shapes lake-atmosphere thermal contrast and synchrony globally - Zhirong Yu; Gang Li; R. Iestyn Woolway; Jixiang Yang; Jiaming Hu; Juan Tao; Kun Shan; Kun Shi; Yunlin Zhang; Lian Feng; Erik Jeppesen; Qichao Zhou (Science Bulletin, 2026)

3D laser scanning-based geometry reconstruction and stress evaluation of a KK-type cast steel node for offshore wind turbine jacket structures - Feng Shi; Hui Jin; Lu Xu; Jiaming Liu; Jiahao Hu; Haihan Jiao (Ocean Engineering, 2026)

Exposure of a sea anemone model for coral biology to the phototoxic sunscreen components dioxybenzone and avobenzone and their metabolites - Jiaming Lily Shi; Djordje Vuckovic; Geraldine L. Keat; John R. Pringle; William A. Mitch (Coral Reefs, 2026)

A bibliometric analysis of global duckweed research (2015–2025): research trends, international collaborations, and emerging themes - Jiaming Wang; Zhenghong Peng; Zuoyue Duan; Yaojun Zhou; Hongling Zhu; Shijun You; Zhiyi Peng; Mengni Shi; Qulian Guo; Wenjun Liu; Ling Guo (Hydrobiologia, 2026)

Identifying the environmental drivers of the distribution of carbon isotopes in global inland waters - Jiahui Shi; Lixiao Ni; Jiaming Liu; Yushen Ma; Yiping Li; Carlo Gualtieri (Water Research, 2026)

Mechanical behavior of marine coral sand - coral clay mixtures reinforced with bionic honeycomb polymer grid: Experimental and artificial intelligence methods - Kaiwei Xu; Jiaqi Luo; Jiaming Zhao; Danda Shi; Zhiming Chao; Titi Sui (Ocean Engineering, 2026)

Ionic liquid-modulated Co/Ni heterostructure MOF nanoflower for efficient electrochemical conversion from HMF to FDCA - Shucan Qin; Weizhen Kong; Anshuang Wu; Longmei Shi; Yuhui Ci; Yunqian Ma; Na Wang; Jiaming Mao (Journal of Environmental Chemical Engineering, 2026)

Design of a green certificate differentiated issuance mechanism based on renewable energy enterprises subsidy perspective: A case study of China - Qinliang Tan; Chaofan Shi; Jiabin Zeng; Zihan Jin; Yihong Ding; Jiaming He; Guangyu Qin (Energy Policy, 2026)

Evaluating aeration rate modulation to restructure denitrifier communities for nitrous oxide mitigation in cattle manure composting using a novel integrated analytical framework - Yu Sun; Xiran Zhou; Jiaming Fan; Lei Sun; Shuai Shi; Xiuhong Xu (Journal of Environmental Management, 2026)

Synergizing machine learning and interpolation methods: A Stacking framework for global-scale satellite soil moisture gap filling - Jiaming Rong; Jiangyuan Zeng; Kun-Shan Chen; Hongliang Ma; Pengfei Shi; Husi Letu; Xiang Zhang; Xihui Gu; Haiyun Bi; Chunlin Zhang (Remote Sensing of Environment, 2025)

Ionic liquid-derived fluorine doped high entropy metal oxides as efficient electrocatalysts for sulfion valorization - Longmei Shi; Anshuang Wu; Shengyun Xu; Jinbiao Liang; Shucan Qin; Jiaming Mao; Yanrong Liu; Yunqian Ma (Journal of Environmental Chemical Engineering, 2025)

Thermophilic antagonistic/competitive networks drive low nitrogen loss in Phase I commercial composting: Deciphering microbe-nitrogen coupling using the novel multistep interaction validation analysis - Yu Sun; Jiaming Fan; Yue Zhang; Zhaoxue Gai; Shuai Shi; Xiuhong Xu (Journal of Environmental Chemical Engineering, 2025)

Stable precursor-ink strategy for inkjet-printed high-temperature oxide films: Towards scalable ITO/In2O3 fabrication - Bian Tian; Jiaming Lei; Zhongkai Zhang; Yedi Zhou; Heng Li; Meng Wang; Shuimin Li; Xu Fan; Guoliang Zhou; Zhaojun Liu; Peng Shi (Chemical Engineering Journal, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Investigation on hydraulic conductivity reduction for silty sand by enzyme induced calcium carbonate precipitation considering urease activity and cementing solution concentration - Lei Shi; Liuhui Huo; Jiaming Fang; Xiangchun Xu; Jianwei Zhang (Engineering Geology, 2025)

Co-incorporation of lattice S and P into nano zero-valent iron induces multiple Kirkendall effects for enhanced trichloroethylene reduction efficiently - Yinghao Shi; Honghong Lyu; Saisai Guo; Jiaming Guo; Feilong Gao; Jingchun Tang (Journal of Hazardous Materials, 2025)

Water quality prediction at large-Scale: Systematic assessment of decomposition-deep learning models - Jiahui Shi; Lixiao Ni; Jiaming Liu; Hui Chen; Yushen Ma; Yi Zhang; Qingwei Lin; Zhen Zhang; Hang Xu; Yiping Li (Journal of Cleaner Production, 2025)

Nutrient dynamics in the East China Sea: Seasonal changes, budget, and ecological impacts - Xiaosong Zhong; Jiaming Liu; Mengjiao Shi; Xiaotian Liu; Zongqing Lv; Xiangbin Ran (Progress in Oceanography, 2025)

Study on hot spot stress distribution and fatigue life assessment of KK-type cast steel nodes based on scaled model test - Haihan Jiao; Jiaming Liu; Lu Xu; Feng Shi; Hui Jin; Yongchun Fan (Ocean Engineering, 2025)

Global-scale gap filling of satellite soil moisture products: Methods and validation - Chunlin Zhang; Jiangyuan Zeng; Pengfei Shi; Hongliang Ma; Husi Letu; Xiang Zhang; Panshan Wang; Haiyun Bi; Jiaming Rong (Journal of Hydrology, 2025)

FeS/rGO modified cathode for enhanced electrochemical activity and TCE degradation in PS-MFC system - Chunji Li; Guanlin Chen; Jiaming Guo; Yinghao Shi; Jikun Li; Jingchun Tang (Journal of Environmental Chemical Engineering, 2025)

ADAM17 promotes colorectal cancer migration and invasion by regulating the TGF-β/Smad signaling pathway - Jiaming Li; Tingjin Zheng; Yingzhi Xu; Mengcha Tian; Liangpan Shi; Jintu Chen; Tian Li; Zhishan Zhang (Tissue and Cell, 2025)

Dual redox-centered p(thiophene-TPA) conjugated polymers for high-performance flexible electrochromic supercapacitors - Xu Cheng; Chunhui Du; Jiaming Li; Yuqiao Zhang; Wenyuan Xu; Jianming Zhang; Hui Shi; Ge Zhang; Long Zhang (Chemical Engineering Journal, 2025)

Correction: Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2025)

pLM33 provides tolerance of persistent Listeria monocytogenes ST5 to various stress conditions and also enhances its virulence - Xin Liu; Tianqi Shi; Jiaming Li; Huanyu Wu; Qing Zhao; Zhixin Fang; Yingying Liang; Quan Xiao; Min Chen; Qingli Dong; Hongzhi Zhang (Food Microbiology, 2025)

Rheological and thermal property of KH570-modified nano-SiO2 grafted xanthan gum and its application in drilling fluid system - Jingqi Shi; Long Chen; Ruihan Xie; Jiayin Zhang; Shuangcheng Pi; Jiaming Yang; Yunhai Zhao; Feng Xiong; Yongkui Zhang; Tonghui Xie (Carbohydrate Polymers, 2025)

Efficient Removal of Cr(VI) by Bamboo-Derived Biochar Supported Nano Zero-Valent Iron: Insights into Performance and Mechanism - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Yunlong Zhu; Jianbing Lu; Yang Gao; Mingjuan Zhang; Wenjing Xue (Water, Air, & Soil Pollution, 2025)

Mechanistic insights into the hydrogel-supported catalyst for superior oxygen evolution performance - Yuxuan Wei; Lingling Xu; Kefan Shi; Hanwen Gong; Jiaming Hu; Xianghao Zhang; Meilan Pan; Edison Huixiang Ang (Chemical Engineering Journal, 2025)

Acoustic micromixing in a serpentine channel with sharp teeth for controllable nanomaterial synthesis - Bin Ran; Bo Liu; Chaozhan Chen; Wenqiang Tong; Jiaming Shi; Jiaxi Du; Zhihang Yu; Siwei Bai; Huaying Chen; Yonggang Zhu (Chemical Engineering Journal, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Development of a portable multi-step microfluidic device for point-of-care nucleic acid diagnostics - Lulu Shi; Zirui Pang; Jianghao Yu; Jiaming Zhu; Xiaohong Xie; Shiling Xie; Lichuan Gu; Wei Hu; Hai Xu; Ling Li; Jifang Tao; Mingyu Wang (Analytica Chimica Acta, 2025)

Study on strength and reduction characteristics of iron ore powder-green carbon composite briquettes - Yifan Chai; Shijie Wang; Jiaming Zhang; Yanshuo Shi; Peijun Liu; Shengli An; Chuan Wang; Xiaojun Ning (Fuel, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

Noise reduction and analysis of leaf electrical signals of strap-leaved plants based on VMD-EWT - Jiaming Gu; Fangming Tian; Jingxiu Shi; Feng Tan (Computers and Electronics in Agriculture, 2024)

Evaluation of a novel attapulgite loaded sulfidized nanoscale zero-valent iron for immobilization of Pb in sediment: Performance, microenvironmental response, and mechanisms - Siqi Wen; Weilong Lin; Qi He; Yiqun Xu; Xiaoyu Shi; Jiaming Guo; Yang Gao; Wenjing Xue (Chemical Engineering Journal, 2024)

Amino-modified biochar-supported S-nZVI for Cr(VI) and total Cr removal from water: Parameter regulation, kinetic and mechanistic analysis - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Qi He; Weilong Lin; Yu Wang; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Water Process Engineering, 2024)

Enhanced reductive degradation of trichloroethylene by ball milled nitridation of bimetallic Ni-ZVI: Combination effect of electron transfer and catalytic hydrogenation - Yinghao Shi; Dong Wang; Jiaming Guo; Feilong Gao; Linan Liu; Jingchun Tang (Journal of Cleaner Production, 2024)

Hydrocarbon Source and Relationship between Hydrocarbon Charging Process and Reservoir Tight Period of the Denglouku Formation Tight Sandstone Gas Reservoirs in the Xujiaweizi Fault Depression, Songliao Basin - Huan Miao; Zhenxue Jiang; Jiaming Lu; Chengju Zhang; Lidong Shi; Lidong Sun; Liang Yang; Peng Shang (Natural Resources Research, 2024)

Informer-Based Model for Long-Term Ship Trajectory Prediction - Caiquan Xiong; Hao Shi; Jiaming Li; Xinyun Wu; Rong Gao (Journal of Marine Science and Engineering, 2024)
Ship trajectory prediction is a complex time series forecasting problem that necessitates models capable of accurately capturing both long-term trends and short-term fluctuations in vessel movements. While existing deep learning models excel in short-term predictions, they struggle with long-sequence time series forecasting (LSTF) due to difficulties in capturing long-term dependencies, resulting in significant prediction errors. This paper proposes the Informer-TP method, leveraging Automatic Identification System (AIS) data and based on the Informer model, to enhance the ability to capture long-term dependencies, thereby improving the accuracy of long-term ship trajectory predictions. Firstly, AIS data are preprocessed and divided into trajectory segments. Secondly, the time series is separated from the trajectory data in each segment and input into the model. The Informer model is utilized to improve long-term ship trajectory prediction ability, and the output mechanism is adjusted to enable predictions for each segment. Finally, the proposed model’s effectiveness is validated through comparisons with baseline models, and the influence of various sequence lengths Ltoken on the Informer-TP model is explored. Experimental results show that compared with other models, the proposed model exhibits the lowest Mean Squared Error, Mean Absolute Error, and Haversine distance in long-term forecasting, demonstrating that the model can effectively capture long-term dependencies in the trajectories, thereby improving the accuracy of long-term vessel trajectory predictions. This provides an effective and feasible method for ensuring ship navigation safety and advancing intelligent shipping.

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

High performance self-assembled sulfidized nanoscale zero-valent iron for the immobilization of cadmium in contaminated sediments: Optimization, microbial response, and mechanisms - Yiqun Xu; Hongdou Liu; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Qi He; Weilong Lin; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Hazardous Materials, 2024)

Affecting factors and mechanism of removing antibiotics and antibiotic resistance genes by nano zero-valent iron (nZVI) and modified nZVI: A critical review - Wenjing Xue; Xiaoyu Shi; Jiaming Guo; Siqi Wen; Weilong Lin; Qi He; Yang Gao; Rongzhong Wang; Yiqun Xu (Water Research, 2024)

Aggregation, retention and transport of γ-MnO2 nanoparticles in water-saturated porous media: Impact on the immobility of thallium - Jiaming Luo; Dafeng Cai; Lezhang Wei; Hang Shi; Yu Liu; Haiqi Yan; Dinggui Luo; Tangfu Xiao; Xuexia Huang; Qihang Wu (Environmental Pollution, 2024)

Effect of Stratified Flow on the Vibration of Anchor Cables in a Submerged Floating Tunnel - Jiaming Xiong; Song Sang; Xiao Shi; Chaojie Gan (Journal of Marine Science and Engineering, 2024)
This study investigates the vertical-type submerged floating tunnel with anchor cables. Based on the characteristics of the anchor cables, the anchor cables are simplified as a nonlinear beam model with hinged ends. Disregarding the axial displacement of the tunnel body, the loads will cause displacements in the x and z directions of the tunnel body. The vibrations of the anchor cables are decomposed into three directions, and the parameter excitation at the connection point between the anchor cables and the tunnel body is taken into account. The equations of motion for the three degrees of freedom of the anchor cables are established using Hamilton’s principle, and then the three equations are solved using the Galerkin method and the fourth-order Runge–Kutta method. The basic characteristics of an internal wave stratified flow acting on the anchor cables are considered, as well as the influence of the incident angle of the ocean currents on the three degrees of freedom of the anchor cables. The results indicate that (1) stratified flow weakens the first- and third-order vortex-induced vibrations of the anchor cables while enhancing the second-order vortex-induced vibrations. When considering the parameter excitation of the anchor cables, the first- and third-order vibrations are weakened, while the second-order vibration remains significant; (2) the first-order vibration of the anchor cables reaches its maximum value when the transverse oscillation frequency of the tunnel body is twice its natural frequency, and the second-order vibration of the anchor cables reaches its maximum value when the transverse oscillation frequency of the tunnel body is twice its natural frequency; (3) the downstream vibration of the anchor cables increases with the increase in the incident angle of the ocean currents, the cross-flow vibration of the anchor cables decreases with the increase in the incident angle of the ocean currents, and the axial vibration of the anchor cables reaches its maximum value when the incident angle of the ocean currents is 60 degrees; (4) stratified flow weakens the lock-in phenomenon of the anchor cables, and the influence of the 1/2 stratified flow on the vibrations of the anchor cables is greater than the influence of the 1/2 stratified flow.

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Minor chromium passivation of S-ZVI enhanced the long-term dechlorination performance of trichlorethylene: Effects of corrosion and passivation on the reactivity and selectivity - Jiaming Guo; Dong Wang; Yinghao Shi; Honghong Lyu; Jingchun Tang (Water Research, 2024)

Research on anode pressure control and dynamic performance of proton-exchange membrane fuel cell system for vehicular application - Heng Wei; Changqing Du; Xingyi Li; Chenxu Shi; Jiaming Zhang (Fuel, 2024)

Activation of persulfate by biochar-supported sulfidized nanoscale zero-valent iron for degradation of ciprofloxacin in aqueous solution: process optimization and degradation pathway - Wenjing Xue; Xinyu Chen; Hongdou Liu; Jun Li; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2024)

Enhanced immobilization of cadmium in contaminated paddy soil by biochar-supported sulfidized nanoscale zero-valent iron - Yiqun Xu; Shan Cao; Xinyu Chen; Jun Li; Hongdou Liu; Yang Gao; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Wenjing Xue (Journal of Soils and Sediments, 2024)

Spatiotemporal distribution of phytoplankton community structure and its relationship with environmental factors in Hongze Lake, China - Jiahui Shi; Lixiao Ni; Jiaming Liu; Chen Xu; Jianhua Zhang; Xuqing Chen (Urban Climate, 2023)

Exploring year-to-year spatiotemporal changes in cycling patterns for bike-sharing system in the pre-, during and post-pandemic periods - Xiaoying Shi; Junjie Zhao; Jiaming He; Haitao Xu (Sustainable Cities and Society, 2023)

Immobilization of cadmium in river sediments by different modified nanoscale zero-valent iron: performance, mechanisms, and Fe dissolution - Wenjing Xue; Hongdou Liu; Jun Li; Xinyu Chen; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Shan Cao; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Biological treatment as a green approach for enhancing electrochemical performance of wood derived carbon based supercapacitor electrodes - Jiaming Cao; Lin Lin; Jian Zhang; Feng Zhao; Junyou Shi; Fachun Guan; Dongliang Wang (Journal of Cleaner Production, 2023)

Recent advances in sulfidized nanoscale zero-valent iron materials for environmental remediation and challenges - Wenjing Xue; Jun Li; Xinyu Chen; Hongdou Liu; Siqi Wen; Xiaoyu Shi; Jiaming Guo; Yang Gao; Jian Xu; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Tetrabromobisphenol A transformation by biochar supported post-sulfidated nanoscale zero-valent iron: Mechanistic insights from shell control and solvent kinetic isotope effects - Feilong Gao; Mingyi Zhang; Shakeel Ahmad; Jiaming Guo; Yinghao Shi; Xinzuo Yang; Jingchun Tang (Journal of Hazardous Materials, 2023)

Potassium assisted pyrolysis of Chinese Baijiu distillers' grains to prepare biochar as controlled-release K fertilizer - Jiali Cheng; Jiaming Zhang; Xiao Xiao; Yue Yuan; Xuepin Liao; Bi Shi; Suyi Zhang (Science of The Total Environment, 2023)

Depth-dependent drivers of soil aggregate carbon across Tibetan alpine grasslands - Junxiao Pan; Jiawei Shi; Dashuan Tian; Ruiyang Zhang; Yang Li; Yunlong He; Lei Song; Song Wang; Yicheng He; Jiaming Yang; Chunxue Wei; Shuli Niu; et al. (Science of The Total Environment, 2023)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)

Generation of reactive oxygen species through dissolved oxygen activation on defected porous carbon for efficient degradation of antibiotics - Jiaming Liu; Zhangwei Yao; Genping Qiu; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; Wenjing Yuan; Peihai Ju; Ruixi Lin; Hengcheng Zhou; et al. (Chemical Engineering Journal, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

Ultrasonic assisted preparation of ultrafine Pd supported on NiFe-layered double hydroxides for p-nitrophenol degradation - Xuan Zhou; Jiaming Shi; Xuefeng Bai (Environmental Science and Pollution Research, 2022)

Ultrasonic-assisted synthesis of highly stable RuPd bimetallic catalysts supported on MgAl-layered double hydroxide for N-ethylcarbazole hydrogenation - Xiaoran Liu; Jiaming Shi; Xuefeng Bai; Wei Wu (Environmental Science and Pollution Research, 2022)

Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2021)

A study on the effects of anion, cation, organic compounds, and pH on the release behaviors of As and Sb from sediments - Haibo Wang; Jiaming Xu; Mario Alberto Gomez; Zhongliang Shi; Yongfeng Jia (Environmental Science and Pollution Research, 2021)